Als cent anys de la mort de Constantí Llombart - Ventura, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
1993 was the centenary celebration of the death of writer, journalist and politician Carmel Navarro Llombart, more commonly known by his pseudonym Constantí Llombart. The speech by Vicent Ventura at the celebration organized by the University of Valencia takes a look at the highlights in the life of Llombart and his statements in favor of recuperating Catalan language and culture, in opposition to the groups that would ultimately dominate during the Renaixença in the Valencian Country.